KELOMPOK PERTEMANAN MAHASISWA SOSIOLOGI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Serli Sitanggang; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Social interaction can be the beginning of the formation of a group, especially in a game environment. One example is in the campus environment, where in general all students always form a friendship group. Through the interactions that occur between students, they will later form friendship groups. A social group tends not to be a static group, but is always developing and experiencing changes, both in activities and form. This study aims to determine the form of groups that exist among students and to find out the similarities that influence the form of friendship groups among sociology students, the Faculty of Social Sciences and Political Science, Riau University. This study used descriptive quantitative research methods with a population of 69 students with a total sample of 69 respondents who were obtained by saturated sampling techniques by taking as many samples as the population. How do you collect data using the questionnaire method. The theory used is the community type theory put forward by Tonnies. The results of this study concluded that of the 3 types of association, the most dominating similarity in forming friendship groups was the form of groups because of the same ideas and thoughts. By having the same idea, the goals in the group can be achieved properly. Keywords:SociologyStudents,FriendGroup